1994
DOI: 10.1007/bf00225152
|View full text |Cite
|
Sign up to set email alerts
|

A study of genetic variation and evolution of Phyllostachys (Bambusoideae: Poaceae) using nuclear restriction fragment length polymorphisms

Abstract: Phylogenetic and taxonomic difficulties are common within the woody bamboos, due to their unique life cycle, which severely limits the availability of floral characters. To addresss some of these problems, 20 species of woody bamboos in the genus Phyllostachys were analyzed using nuclear restriction fragment length polymorphisms (RFLPs). The RFLP data were used to generate genetic distances between all pairs of taxa and to examine the degree of genetic variation within and among bamboo species. The genetic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 8 publications
3
24
1
1
Order By: Relevance
“…1997). The assertion that P. nigra belongs to section Heteroclada is also congruent with the results of a nuclear RFLP study by Friar and Kochert (1994). Phyllostachys aureosulcata is intermediate in morphology between sections Heteroclada and Phyllostachys and was placed by Renvoize and Hodkinson (1997) in a revised section Heteroclada on the basis of its morphology.…”
Section: Aflpsupporting
confidence: 73%
See 1 more Smart Citation
“…1997). The assertion that P. nigra belongs to section Heteroclada is also congruent with the results of a nuclear RFLP study by Friar and Kochert (1994). Phyllostachys aureosulcata is intermediate in morphology between sections Heteroclada and Phyllostachys and was placed by Renvoize and Hodkinson (1997) in a revised section Heteroclada on the basis of its morphology.…”
Section: Aflpsupporting
confidence: 73%
“…(1980). Friar and Kochert (1994) assessed variation at the DNA sequence level using restriction fragment length polymorphisms (RFLPs) and found that the taxa clustered into two broad groups when assessed with both genetic distance methods and phylogenetic methods using maximum parsimony. Their results were in broad agreement with the morphological classification of Wang et a/.…”
mentioning
confidence: 99%
“…The cluster analysis indicates that 12 taxa belonging to different genera of bamboo formed two major clusters based on similarity indices. Both major clusters were further divided into (Friar and Kochert 1994) and RAPD (Gielis et al 1997). Besides, the divergence was higher between the genus Sasa and Bambusa, Bambusa and Dendrocalamus.…”
Section: Resultsmentioning
confidence: 99%
“…Many molecular approaches, such as RAPD (Random Amplified Polymorphism DNA), AFLPs (Amplified Fragment Length Polymorphisms) and RFLPs (Restriction Fragment Length Polymorphisms) have been used in studies of bamboo genetic variability (Friar and Kochert 1994, Lai and Hsiao 1997, Hodkinson et a/. 2000.…”
mentioning
confidence: 99%